THE SYSTEM OF HIGHER EDUCATION IN ITALY AND UKRAINE - Tavrin, A.; Pevnev, V. (Systems and Technologies, 2019)
The proposed paper provides a comparative description of higher education systems in Ukraine and Italy. The comparison was carried out on nine indicators that were taken from international publications and ratings of universities in the world. Some publications relate to Italian sources, and some to Ukrainian. The number of national universities in Italy and Ukraine that were included in the QS World University Rankings 2020 rating was considered. All these data are shown in the table. The organization of the educational process at universities in Italy is based on the great independence of students. Students, choosing a specialty, have a list of subjects for study, each of which has its own weight – credit. Among sub-jects, students independently choose the discipline to study, gaining the required number of credits. In Ukraine, the existing system assumes the existence of com-pulsory disciplines (75 %) and disciplines of students’ choice (25 %). The fea-tures of the construction of the educational process in Italian universities are considered. The discipline “Project and Team Management Methodologies”, taught at the University of Trento, was chosen as an example. One of the distin-guishing features of training in this discipline is the practical orientation of stu-dents’ independent work, starting with the choice of topic and ending with the practical implementation of the work done. When analyzing the use of infor-mation technologies in the educational process, it is shown that they are being used starting from the first step of a student in Italian universities. This is due to the very good organization of the educational process, the involvement of students in the preparation and conduct of classes, the organization of their independent work, approaches to teaching independent decision making and responsibility for their implementation. In this regard, requirements for lecturer are increasing. Video shooting of the lecture, which is conducted by students, requires more thorough preparation of the lecturer, in-depth knowledge of the material presen- ted, the ability to keep all students under control and the ability to remain “in the frame”. The possibility of introducing the presented experience into the educa-tional process of Ukrainian universities is shown.